Intracellular Calcium Release at Fertilization in the Sea Urchin Egg - Steinhardt, R. (Dev Biol, 1977)
Fertilization or ionophore activation of Lytechinus pictus eggs can be monitored after injection with the Ca-sensitive photoprotein aequorin to estimate calcium release during activation. We estimate the peak calcium transient to reach concentrations of 2.5–4.5 μM free calcium 45–60 sec after activation and to last 2–3 min, assuming equal Ca(2+) release throughout the cytoplasm. Calcium is released from an intracellular store, since similar responses are obtained during fertilization at a wide range of external calcium concentrations or in zero-calcium seawater in ionophore activations. In another effort to estimate free calcium at fertilization, we isolated egg cortices, added back calcium quantitatively, and fixed for observation with a scanning electron microscope. In this way, we determined that the threshold for discharge of the cortical granules is between 9 and 18 μM Ca(2+). Therefore, the threshold for the in vitro cortical reaction is about five times the amount of free calcium, assuming equal distribution in the egg. This result suggests that transient calcium release is confined to the inner subsurface of the egg.